Sequential versus simultaneous contributions to public goods: experimental evidence - Simon Gächter; Daniele Nosenzo; Elke Renner; Martin Sefton (Center for Economic Studies and ifo Institute (CESifo), 2009)
We report an experiment comparing sequential and simultaneous contributions to a public good in a quasi-linear two-person setting (Varian, Journal of Public Economics, 1994). Our findings support the theoretical argument that sequential contributions result in lower overall provision than simultaneous contributions. However, the distribution of contributions is not as predicted: late contributors are sometimes willing to punish early low contributors by contributing less than their best response. This induces early contributors to contribute more than they otherwise would. A consequence of this is that we fail to observe a predicted first mover advantage.
Keywords: C92; D03; H41; 330; Public goods; voluntary contributions; sequential moves; experiment; Öffentliches Gut; Spende; Spieltheorie; Test